MicroRNA‐20a in extracellular vesicles derived from duodenal fluid is a possible biomarker for pancreatic ductal adenocarcinoma - Takashi Taniguchi; Noboru Ideno; Tomoyuki Araki; Shun Miura; Masahiro Yamamoto; Tomoki Nakafusa; Nobuhiro Higashijima; Takeo Yamamoto; Koji Tamura; So Nakamura; Toshiya Abe; Naoki Ikenaga; et al. (DEN Open)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) has a high mortality rate owing to its late diagnosis and aggression. In addition, there are relatively few minimally invasive screening methods for the early detection of PDAC, making the identification of biomarkers for this disease a critical priority. Recent studies have reported that microRNAs in extracellular vesicles (EV‐miRs) from bodily fluids can be useful for the diagnosis of PDACs. Given this, we designed this study to evaluate the utility of cancer EVs extracted from duodenal fluid (DF) and their resident EV‐miRs as potential biomarkers for the detection of PDAC. Methods EV‐miRs were evaluated and identified in the supernatants of various pancreatic cancer cell lines (Panc‐1, SUIT2, and MIAPaca2), human pancreatic duct epithelial cells, and the DF from patients with PDAC and healthy controls. EVs were extracted using ultracentrifugation and the relative expression of EV‐miR‐20a was quantified. Results We collected a total of 34 DF samples (27 PDAC patients and seven controls) for evaluation and our data suggest that the relative expression levels of EV‐miR‐20a were significantly higher in patients with PDAC than in controls (p = 0.0025). In addition, EV‐miR‐20a expression could discriminate PDAC from control patients regardless of the location of the tumor with an area under the curve values of 0.88 and 0.88, respectively. Conclusions We confirmed the presence of EVs in the DF and suggest that the expression of EV‐miR‐20a in these samples may act as a potential diagnostic biomarker for PDAC.